Kesesuaian Sistem Proporsional Terbuka dalam Pemilihan Umum Indonesia - Gulo, Titonius; Suhartono, Slamet (CV. Era Digital Nusantara, 2023)
General elections are a form of manifestation of the democratic system adopted by every country that applies democratic values. The implementation of elections is not only used as a form of necessity for government power in carrying out the leadership period but also to be used as a means of infrastructure for the people to articulate aspirations and interests in everyday life. The people can also elect their representatives who will later occupy seats in parliament as members of the legislature. The legal basis for organizing legislative elections in Indonesia has continued to change since the reform era began. Changes to election laws are always made before an election is held, based on an assessment of the results of previous elections for other reasons. This change, of course, coincided with the revision of the law on election administration and the law on political parties. This legal reform package is also known as the main legal reform package. Gaps in statutory regulations can also lead to different interpretations of the implementation of certain rules. The decision of the Constitutional Court which abolished the electoral system which limited the counting of votes demonstrated the inadequacy of the election regulations.